Macrophage migration inhibitory factor promotes the migration of dendritic cells through CD74 and the activation of the Src/PI3K/myosin II pathway. Issue 5 (28th March 2021) - Ives, Annette; Le Roy, Didier; Théroude, Charlotte; Bernhagen, Jürgen; Roger, Thierry; Calandra, Thierry
Abstract: Constitutively expressed by innate immune cells, the cytokine macrophage migration inhibitory factor (MIF) initiates host immune responses and drives pathogenic responses in infectious, inflammatory, and autoimmune diseases. Dendritic cells (DCs) express high levels of MIF, but the role of MIF in DC function remains poorly characterized. As migration is critical for DC immune surveillance, we investigated whether MIF promoted the migration of DCs. In classical transwell experiments, MIF −/− bone marrow‐derived DCs (BMDCs) or MIF +/+ BMDCs treated with ISO‐1, an inhibitor of MIF, showed markedly reduced spontaneous migration and chemotaxis. CD74 −/− BMDCs that are deficient in the ligand‐binding component of the cognate MIF receptor exhibited a migration defect similar to that of MIF −/− BMDCs. Adoptive transfer experiments of LPS‐matured MIF +/+ and MIF −/− and of CD74 +/+ and CD74 −/− BMDCs injected into the hind footpads of homologous or heterologous mice showed that the autocrine and paracrine MIF activity acting via CD74 contributed to the recruitment of DCs to the draining lymph nodes. Mechanistically, MIF activated the Src/PI3K signaling pathway and myosin II complexes, which were required for the migration of BMDCs. Altogether, these data show that the cytokine MIF exerts chemokine‐like activity for DC motility and trafficking.